Temporary anchorage devices in clinical orthodontics - Park, Jae Hyun 1963- (Hoboken, New Jersey Wiley-Blackwell, 2020)
"Written by some of the world's leading experts in orthodontics, Temporary Anchorage Devices in Clinical Orthodontics is a comprehensive, up-to-date reference that covers all aspects of temporary anchorage device (TAD) use in contemporary orthodontics. Taking a real-world approach to the subject, it covers topics ranging from diagnosis and treatment planning to the many applications and management of complications. Case studies demonstrate the concepts, and high-quality clinical photographs support the text throughout. The book begins with an overview of clinical applications and fundamental principles of TADs. It then goes on to cover biomechanical considerations for controlling target tooth movement with TADs. Biomechanical simulations for various clinical scenarios treated with TADs are addressed next, followed by an examination of histological aspects during the healing process and anatomical considerations with TADs. Other chapters cover: Class II Correction with TADs, Distalization with TADs, TAD-anchored Maxillary Protraction, Maxillary Expansion with TADs, Anterior Open Bite Correction with TADs, TAD-assisted Aligner Therapy, TADs vs. Orthognathic Surgery; Legal Considerations When Using TADs; and much more. Temporary Anchorage Devices in Clinical Orthodontics is an essential resource for orthodontists and orthodontic residents. Provides evidence-based information on the use of TADs, with a focus on improving outcomes for patients. Considers topics ranging from diagnosis and treatment planning to specific clinical applications and appliances. Takes a real-world clinical approach, with case studies demonstrating concepts. Written by international experts in the field. Presents hundreds of high-quality clinical photographs to support the text"--
Contents; Section I: Fundamental Perspectives on TADs; 1. An Overview of Clinical Applications for Temporary Anchorage Devices (TADs); 2. Biomechanical Considerations for Controlling Target Tooth Movement with Mini-implants; 3. Biomechanical Simulations for Various Clinical Scenarios Treated with TADs; 4. Histological Aspects During the Healing Process with TADs; 5. The Effects of TADs on the Alveolar Bone; 6. Mechanical Aspects of TADs; 7: Factors Affecting the Failure of TADs and Efforts to Improve the Biomechanical Stability of TADs; 8: TADs and Successful Clinical Outcomes; 9. Clinical, Mechanical, and Diagnostic Indices for the Placement of TADs; 10. Considerations for the Placement of TADs; 11. Understanding Implant Sites for TADs; 12. Palatal TADs: Anatomical Considerations; 13. Implant Site Selection; Section I: Three-dimensional correction with TADs; 14. Treating Skeletal Class II Hyperdivergent Patients: A Structured Decision-making Process; 15. Class II Correction with Skeletal Anchorage and Forsus; 16. Distalization of Maxillary and Mandibular Molars with TADs; 17. Effective Treatment of Class II Maloccusion with the TAD-supported amda; 18. The Use of TADs with a Wilson Distalizing Arch; 19. The Use of TADs to Correct Challenging Class II Sagittal Discrepancies; 20. Dentofacial Orthopedics for Class III Corrections with Bone-anchored Maxillary Protraction; 21. TAD-anchored Maxillary Protraction; 22. Protraction Headgear with Surgical Miniplates; 23. Total Arch Distalization and Control of Transverse Discrepancy with TADs; 24. Maxillary Expansion in Skeletally Mature Patients with TADs; 25. Maxillary Expansion with TADs in Young Adults; 26. TAD-assisted Naso-maxillo-pharyngeal Expansion; 27. Scissor Bite Correction with TADs; 28. Clinical Outcomes with TADs and Conventional Mechanics in Adult Skeletal Open Bite and Class II Patients; 29. Control of Vertical Dimension and Chin Position in Class II Malocclusion with Miniscrew Implants; 30. Anterior Open Bite Correction with One Midpalatal TAD; 31. Treatment of Open Bite with TADs: The Nature of Molar Intrusion and Relapse; 32. Double Arch Intrusion: Effective Use of TADs to Correct Vertical Excess; Section III: Clinical Applications of TADs; 33. Three-dimensional Application of Orthodontic Miniscrews and Their Long-term Stability; 34. Tweed-Merrifield Directional Force Technology with TADs; 35. Non-extraction Treatment of Class II Hyperdivergent Patients with Orthodontic Mini-implants; 36. Clinical Application of Palatal TADs; 37. Management of Missing Teeth with C-implants; 38. Indirect Miniscrew Anchorage for Adjunctive Orthodontic Treatment: Clinical Applications and Stability; 39. TADs for Limited Orthodontic Treatment; 40. Uprighting Impacted Mandibular Second Molars with a Cantilever System Using TADs; 41. Orthodontic Treatment of TMD Patients with Posterior Intrusion Using TADs; 42. Insights to Extraradicular Bone Screw Applications for Challenging Malocclusions; 43. The Biomechanics of Extra-alveolar TADs in Orthodontics; 44. A New and Innovative TAD System for Improved Stability and Versatility; 45. Palatal and Ramal Plate Applications; 46. Miniscrews vs. Miniplates; 47. Progress of Anchorage in Lingual Orthodontics Treatment; 48. Biomechanics of Lingual Orthodontics and TADs; 49. TADs with a Fully Customized CAD-CAM Lingual Bracket System; 50. TAD-assisted Lingual Retractors; 51. TADs and Invisalign: Making Difficult Movement Possible; 52. The Use of TADs with Clear Aligners for Asymmetry Correction; 53. Microimplant-assisted Aligner Therapy; 54. Safe and Precise TAD Placement in the Anterior Palate with Simple and Inexpensive TAD Guides; Section IV. Esthetic Control with TADs; 55. Correction of Occlusal Canting with TADs; 56. Treatment of Facial Asymmetry with Microimplants; 57. Facial Asymmetry: Non-surgical Orthodontic Treatment Considerations; 58. The Application of TADs for Gummy Smile Correction; 59. Application of TADs in an Adult Gummy Smile Case with Vertical Maxillary Excess; 60. Facial Esthetics-oriented Treatment Planning with Dental VTOs and TADs; 61. Improved Facial Profile with Premolar Extraction and Molar Intrusion Using TADs and VTOs; Section V: Application of TADs in Surgical Cases. 62. TADs vs. Orthognathic Surgery; 63. Advantages of Miniscrew Usage for Pre- and Post-operative Orthodontics in Skeletal Class III Malocclusion Patients; 64. Orthodontic Biomechanics with Miniplates in the Surgery-first Orthognathic Approach; Section VI: Complications with the Use of TADs; 65. Biomechanical Mistakes Related to the Use of TADs; 66. Pros and Cons of Miniscrews and Miniplates for Orthodontic Treatment; 67. Orthodontic Miniscrews: The Pearls and Pitfalls of TADs; 68. Success with TADs: Evidence and Experience; 69. Legal Considerations when Using TADs; Index
UP System perpetual contents
Includes bibliographical references and index
Keywords: Orthodontics